Структурная и параметрическая оптимизация локальной подсистемы инженерной сети - Федоров, Николай Викторович; Хренов, Александр Михайлович (НТУ "ХПИ", 2017)
Рассматривается задача определения оптимальной структуры и параметров функционирования локальной подсистемы инженерной сети, при заданных граничных условиях. Локальная подсистема состоит из активных и пассивных элементов, образующих сложную сетевую структуру. Проведена декомпозиция задачи оптимизации локальной подсистемы инженерной сети. Предложены алгоритмы определения оптимального распределения расходов целевого продукта и соответствующих им давлений на входах сети, а также выбора рациональной структуры линейной части магистрального газопровода, в основе которого лежит один вариант поиска коллективом автоматов Буша-Мостеллера.

The problem of determining the optimal structure and parameters of the functioning of a local subsystem of an engineering network, under given boundary conditions, is considered. It is shown that this task has a hierarchical structure, corresponding tasks are formulated for each level of the hierarchy. The local subsystem consists of active and passive elements forming a complex network structure. The solution of the problem of finding the optimal structure and parameters of the active elements of the local subsystem can be obtained by solving the problem of determining the optimal structure of the linear part and the problem of determining the optimal structure and parameters of the compressor station for a given structure of the linear part. Determination of the optimal structure and parameters of the compressor station, in turn, reduces to solving the problem of determining the optimal distribution of gas flow through the inputs of the linear part and the problem of determining the optimal structure and control parameters of the compressor station. Decomposition of the optimization problem of the local subsystem of the engineering network is carried out. Algorithms are proposed for determining the optimal distribution of the target product costs and the corresponding pressures at the grid inputs, as well as choosing the rational structure of the linear part of the main gas pipeline, which is based on one variant of searching for the Bush-Mosteller automata.
Structural and parametric optimization of the local subsystem of the engineering network
Keywords: магистральный газопровод; декомпозиция; рациональная структура; компрессорная станция; КС; optimization; main gas pipeline; decomposition